Urgensi Kader Pemberdayaan Masyarakat Desa dalam Meningkatkan Partisipasi Masyarakat terhadap Pembangunan Desa - Widadi, Teguh; Eldo, Dwian Hartomi Akta Padma (Jurnal Studi Pemerintahan dan Akuntabilitas, 2023)
Purpose: The purpose of this study was to see how big the role played by Community Empowerment Cadres in increasing community participation in Village Development. This research focuses on looking at the performance of community empowerment cadres in Wonosoyoso Village, Kebumen Regency in 2021. The hope of having empowerment cadres in the village is to be able to increase community participation in each village. Method: The method used is a qualitative descriptive approach with data collection techniques by in-depth interviews with each stakeholder. Besides that, it also uses secondary data from books, documents, and news that support this research. Data analysis techniques are carried out after collecting the data needed to further obtain the desired results in research. Result: The role of Community Empowerment Cadres in Wonoyoso Village in increasing community participation in village development, in general, has carried out its roles, duties, and functions, in carrying out functions as intended. Mobilizing and motivating the community to actively participate in development in their area has been effective even though there are still members who play a role passive when activities are not in their area, it needs to be increased so that all members always play an active role in every activity in the village. In addition, community empowerment cadres also receive financial assistance to carry out the program implemented. Limitation: This research is only focused and limited to activities carried out by community empowerment cadres in Wonoyoso Village, Kebumen Regency. So there may be differences regarding activities and urgency with other villages. Contribution: The results of this study are expected to be a good description of community empowerment cadres in other designs. Because this research shows that there is a positive influence from the performance of community empowerment cadres in Wonoyoso Village, Kebumen Regency.